333 Intraventricular Ziconotide Improves Cognitive Outcomes following Lateral Fluid Percussion Injury in a Rat Model. (April 2023) - Jude, Morgan Blair; Izadi, Ali; Shahlaie, Kiarash; Gurkoff, Gene G.
Abstract : INTRODUCTION: Traumatic brain injury (TBI) is a major source of morbidity and mortality worldwide. In previous studies, intravenous ziconotide, a selective N-type voltage-gated calcium channel blocker, reduced brain calcium accumulation, improved brain mitochondrial respiration, and improved cognitive and motor outcomes in rodent models of TBI. Attempts to translate intravenous ziconotide therapy to humans were halted due to peripheral side-effects. However, ziconotide is now FDA-approved for treatment of severe pain syndromes when administered intrathecally instead of intravenously. We hypothesize that following TBI intraventricular ziconotide will improve cognitive function in the absence of significant side effects. METHODS: Seventy-seven Sprague-Dawley rats underwent sham (n = 11 males, n = 11 females) or lateral fluid percussion (LFP) injury (n = 21 males, n = 23 females). One-hour post-injury, rats received either an intraventricular injection of saline (n = 22 sham, n = 23 LFP) or ziconotide (n = 21 LFP). A catheter was implanted in the left lateral ventricle and connected to an Alzet micro-osmotic pump to allow for 72 hours of continuous infusion. Cognitive outcomes were evaluated using Morris water maze (MWM; days 10-15). RESULTS: TBI-saline rats performed significantly worse than shams on MWM (p < 0.01). Ziconotide treated rats had an intermediate phenotype on MWM. TBI-saline rats swam a less efficient path than sham animals (p < 0.01); ziconotide path efficiency was not significantly different from shams. Performance on the MWM was likely not related to motor deficits as there was no significant effect of group on mean swimming speed in either males or females. Female sham animals performed significantly better on probe trials compared to TBI-saline (p < 0.05); ziconotide animals were not different from shams. CONCLUSIONS: These findings support centrally delivered Ziconotide as a potential neuroprotective agent to improve cognitive performance following TBI. Further studies are required to characterize the neuroprotective effects of Ziconotide therapy.